2006
DOI: 10.1017/s002202990600210x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical mastitis in dairy cows in Swiss organic and conventional production systems

Abstract: The objective was to compare the prevalence of subclinical mastitis (SM) and of udder pathogens in 60 Swiss organic (OP) and 60 conventional production systems (CP). Cows (n=970) were studied for SM prevalence and udder pathogens at median 31 d and 102 d post partum. Cows showing a >or=1+ positive California Mastitis Test (CMT) in at least one quarter were considered to have SM. Cow-level prevalences of SM for visits at 31 d and 102 d post partum (39% and 40% in OP and 34% and 35% in CP) were similar, but quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 27 publications
9
34
0
4
Order By: Relevance
“…De maneira similar aos achados do presente estudo, a maior prevalência de mastite subclínica, comparativamente a clíni-ca, em rebanhos bovinos com produção de leite orgânico também tem sido assinalada em outros países, causada predominantemente por microrganismos de origem contagiosa (Guinot- Thomas et al 1991, Roesch et al 2007). Este achado pressupõe que devem ser direcionados esforços no controle da mastite nas quatro propriedades estudadas, priorizando medidas voltadas aos microrganismos contagiosos, que possam ser adequadas à sistemática orgânica de produção, incluindo noções de higiene do ordenhador, manejo adequado na ordenha, adoção de pós-dipping e descarte de animais com mastite crônica.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…De maneira similar aos achados do presente estudo, a maior prevalência de mastite subclínica, comparativamente a clíni-ca, em rebanhos bovinos com produção de leite orgânico também tem sido assinalada em outros países, causada predominantemente por microrganismos de origem contagiosa (Guinot- Thomas et al 1991, Roesch et al 2007). Este achado pressupõe que devem ser direcionados esforços no controle da mastite nas quatro propriedades estudadas, priorizando medidas voltadas aos microrganismos contagiosos, que possam ser adequadas à sistemática orgânica de produção, incluindo noções de higiene do ordenhador, manejo adequado na ordenha, adoção de pós-dipping e descarte de animais com mastite crônica.…”
Section: Resultsunclassified
“…(4,3%), em cultura pura ou em associação (Quadro 2). Esses achados são condizentes com a literatura visto que estes microrganismos são reconhecidos como os principais agentes causais de mastite em bovinos (Langoni et al 1998a, Costa 2001, Santos & Fonseca 2007, incluindo animais manejados no sistema orgânico (GuinotThomas et al 1991, Roesch et al 2007. A mastite é reconhecida como a principal doença que afeta animais de produção direcionados à exploração leiteira, decorrente das alterações provocadas na composição físico-química e na celularidade do leite, dos prejuízos com a redução na produção determinados pelos agravos no tecido glandular, somados aos reflexos na Saúde Pública (Langoni 2000, Ribeiro 2008).…”
Section: Avaliação De Resíduos De Antimicrobianos No Leiteunclassified
“…Other authors reported negative bacteriological findings in 17.7 to 26.5% from cases of clinical mastitis and 28.7 to 38.6% from cases of subclinical mastitis (Roesch et al, 2007).…”
Section: P Aeruginosa β-Laktammentioning
confidence: 99%
“…and Streptococcus spp. was revealed from cases of subclinical mastitis in dairy cows (Roesch et al, 2007;Kalmus et al, 2011). Saini et al (2013) reported higher prevalence of environmental mastitis pathogens and Escherichia coli in dairy herds, predominantly in early lactation.…”
Section: P Aeruginosa β-Laktammentioning
confidence: 99%
“…One study (Garmo et al, 2010) found a significantly lower somatic cell count on organic farms as compared to conventional farms. On the other hand, five papers (Weller and Cooper, 1996;Vaarst and Bennedsgaard, 2001;Nauta et al, 2006;Roesch et al, 2007;Park et al, 2012) found a higher SCC on organic farms as compared to conventional farms. Two of these four studies (Weller and Cooper, 1996;Vaarst and Bennedsgaard, 2001), however, did not provide a level of significance.…”
Section: Dairy Cattlementioning
confidence: 99%